Gut microbe-derived metabolites and the risk of cardiovascular disease in the METSIM cohort - Mirzaei, Sahereh; DeVon, Holli A.; Cantor, Rita M.; Cupido, Arjen; Fernandes Silva, Lilian; Laakso, Markku; Lusis, Aldons J. (Frontiers in Microbiology, 2024)
Background: An association between gut microbes and cardiovascular disease (CVD) has been established but underlying mechanisms remain largely unknown. Methods: We conducted a secondary analysis of cross-sectional data from the METSIM (Metabolic Syndrome In Men) population-based cohort of 10,194 Finish men (age=57.65 ± 7.12 years). We tested the levels of circulating gut-microbe derived metabolites as predictors of CVD, ischemic cerebrovascular accident (CVA), and myocardial infarction (MI). The Kaplan-Meier method was used to estimate the time from the participants first outpatient clinic visit to the occurrence of adverse outcomes. The associations of metabolite levels with the outcomes were assessed with Cox proportional hazard models. Results: During a median follow up of 200 months, 979, 397, and 548 participants experienced CVD, CVA, and MI respectively. After adjustment for traditional risk factors and correction for multiple comparisons, higher plasma levels of succinate (quartile 4 vs. quartile 1; adjusted hazard ratio (aHR=1.30, [CI, 1.10-1.53] p=0.0003. adj. p=0.01) were significantly associated with risk for CVD. High plasma levels of ursodeoxycholic acid (quartile 3 vs. quartile 1); (aHR=1.68, [CI, 1.26-2.2]; p=0.0003, adj. p=0.01) were associated with higher risk of CVA. As a continuous variable, succinate was associated with a 10% decreased risk for CVD (aHR= 0.9; [CI, 0.84-0.97]; P = 0.008) and 15% decreased in risk of MI, (aHR=0.85, [CI, 0.77-0.93]; p=0.0007) respectively. Conclusion: Gut microbe-derived metabolites, succinate and ursodeoxycholic acid were associated with CVD, MI, and CVA. Modulating the gut microbes may represent a potential therapeutic target for modulating CVD and CVA.